Performance of Smart Homes for participating in Electricity Markets - Pedro do Couto Reis e Silva (2021)
Due to the rising energy consumption of residential consumers, smart home consumers' behaviour is being studied in the last years to achieve optimal energy efficiency and power consumption. Also, there is a need to optimize house energy consumption to minimize costs and reduce gas emissions. Nowadays, Electricity Market has been much more competitive due to the rising of renewable energy sources and consumer's active participation in the market, using demand response programs. This project aims to develop and improve a source code to allow demand management of a Smart Home, including renewable energy generation, electric vehicle and other smart appliances and electrical devices. Furthermore, the reduction of the expected cost of energy consumption and the rise of consumer's comfort are considered as goals for the project.